A5.03 Monitoring therapy response of experimental arthritis with radiolabeled tracers targeting fibroblasts, macrophages or integrin αvβ3. (24th February 2016) - Terry, SYA; Walgreen, B; Helsen, MM; Franssen, GM; Nayak, TK; Freimoser-Grundschober, A; Klein, C; Oyen, WJ; Boerman, OC; Laverman, P; Koenders, MI
Abstract : Background and objectives: Monitoring response to therapy in arthritis is usually carried out by clinical assessment, ultrasonography, conventional radiography or MRI. Molecular imaging could be used to more specifically monitor therapy response, thus enabling tailored therapy regimens and enhancing therapeutic outcome. Here, we hypothesised that response to etanercept could be monitored by radionuclide imaging in arthritic mice. We tested three different targets namely fibroblast activation protein (FAP), F4/80-expressing macrophages, and integrin αv β3 . Materials and methods: Male DBA/1J mice with collagen-induced arthritis were treated with etanercept. SPECT/CT (Single photon emission computed tomography/ X-ray computed tomography) scans were acquired at 1, 24 and 48 h after injecting 111 In-RGD2 (integrin αv β3 ), 111 In-anti-F4/80-A3–1 (anti-murine macrophage antibody), or 111 In-28H1 (anti-FAP antibody), respectively, with nonspecific controls included. Mice were dissected after the last scan and scans were analysed quantitatively and were correlated with macroscopic scoring. Results: Experimental arthritis in DBA-1J mice was imaged with 111 In-28H1 (anti-FAP), 111 In-anti-F4/80-A3–1, and 111 In-RGD2 . Tracer uptake in joints correlated signifianty with arthritis score. Treatment decreased joint uptake of tracers; it decreased from 23 ± 15%ID/g, 8 ± 4%ID/g, 2 ± 1%ID/g to 11 ± 11%ID/g (p < 0.001), 4 ± 4%ID/g (p < 0.001), 1 ± 0.2%ID/g (p < 0.01) for 111 In-28H1, 111 In-anti-F4/80-A3–1, and 111 In-RGD2, respectively. Arthritis-to-blood ratios (in mice with established arthritis) were higher for 111 In-28H1 (5.5 ± 1), 111 In-anti-F4/80-A3–1 (10.4 ± 4), and 111 In-RGD2 (7.2 ± 1)than for control 111 In-DP47GS (0.7 ± 0.5; p = 0.002), 111 In-rat IgG2b (0.5 ± 0.2; p = 0.002), or co-injection of excess RGD2, (3.5), indicating specific uptake of all tracers in arthritic joints. Conclusions: In conclusion, 111 In-28H1, 111 In-anti-F4/80-A3–1, and 111 In-RGD2 can be used to specifically monitor therapy response in experimental arthritis at the molecular level. Not only does this highlight the originality of the studies carried out here, by targeting integrins, macrophages or FAP in preclinical models of arthritis, but also the novelty of assessing these tracers as tools to monitor therapy response. Further studies need to be carried out to determine whether these tracers could be used for early diagnosis of arthritis as well as whether they can be used to monitor response to other types of therapies.